2018
DOI: 10.5935/2595-0118.20180017
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial myofunctional disorder, a possible complicating factor in the management of painful temporomandibular disorder. Case report

Abstract: BACKGROUND AND OBJECTIVES:The clinical association between painful temporomandibular disorder and orofacial myofunctional disorders is frequent and requires attention. The objective of this study was to describe a clinical case of painful temporomandibular disorder in association with orofacial myofunctional disorders that evidence the importance of dental and speech therapy approaches involving myofunctional orofacial limits, as well as to discuss whether the presence of orofacial myofunctional disorders can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(46 citation statements)
references
References 18 publications
(32 reference statements)
1
22
0
17
Order By: Relevance
“…As for the construct evaluation, a statistically significant difference was found between the SG and CG regarding the clinical examination of pain on palpation and mandibular mobility. This result corroborates those of studies that reported changes in mandibular mobility (15,16) and sensitivity to palpation on the masticatory and cervical muscles in individuals with TMD (14,24) .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As for the construct evaluation, a statistically significant difference was found between the SG and CG regarding the clinical examination of pain on palpation and mandibular mobility. This result corroborates those of studies that reported changes in mandibular mobility (15,16) and sensitivity to palpation on the masticatory and cervical muscles in individuals with TMD (14,24) .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the content evaluation, the MBGR Protocol includes the analysis of the orofacial structures and habitual posture of lips and tongue that may be altered in cases of TMD (16,19,24) ; mobility of the lips and mandible that may be impaired in this population (14)(15)(16)19) ; masticatory function, for which there is consensus among studies of the presence of disorder in this function (5,(14)(15)(16)(17)(18)(19)(20)(21)26) ; deglutition, referred to as atypical or adapted in cases of TMD (14,16,(19)(20)(21)(22)25) ; speech, allowing identification of cases with phonetic and TMJ disorders (14) . Thus, the MBGR Protocol encompasses the Orofacial Myofunctional Disorders (OMD) described in the literature for individuals with TMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, by correcting these habits simultaneously with dental alignment by using elastodontic dental appliances, it is gaining more and more ground in orthodontic practice [11]. On the other hand, the other alternative approach to these dental diseases is represented by the use of bracket devices that have the disadvantage number, the most important being the high percentage of recurrence [12]. Two of the most elastodontic orthodontic appliances are Myobrace for Kids from Myofunctional Research Co. (Helensvale, Australia) (MB) and LM TrainerTM 2 (LMD).…”
Section: Introductionmentioning
confidence: 99%